2018
DOI: 10.3390/educsci8030112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer Tutoring on the Academic Achievement of Students in the Subject of Biology at Secondary Level

Abstract: The present study is aimed at analyzing the effects of peer tutoring on the academic achievement of students in the subject of biology at secondary level. The objectives of the study were: (1) To find out the effects of peer tutoring on the academic achievement of students in the subject of biology; and (2) To examine the effects of peer tutoring with respect to knowledge, comprehension and application levels in cognitive domain of Bloom Taxonomy. All 433,405 male students at secondary level of 10th grade of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
3
14
0
1
Order By: Relevance
“…Still, there is little evidence in the literature of studies in which peer tutoring combined into the context of solving exponential expressions. The results about peer tutoring are consistent with the study of Bellen & Jomoc (2017), Campit et al, (2015), Chua & Wood (2005) and Ullah, et al, (2018), suggesting that peer tutoring can advance learning outcomes among high school students. Similar findings suggest effective peer tutoring intervention for at-risk students (Bellen & Jomoc, 2017;George, et al, 2015;Mayfield & Vollmer, 2007;Morales, et al, 2016).…”
Section: Students' Learning Outcomes In Solving Exponential Expressions Using Peer Tutoringsupporting
confidence: 87%
“…Still, there is little evidence in the literature of studies in which peer tutoring combined into the context of solving exponential expressions. The results about peer tutoring are consistent with the study of Bellen & Jomoc (2017), Campit et al, (2015), Chua & Wood (2005) and Ullah, et al, (2018), suggesting that peer tutoring can advance learning outcomes among high school students. Similar findings suggest effective peer tutoring intervention for at-risk students (Bellen & Jomoc, 2017;George, et al, 2015;Mayfield & Vollmer, 2007;Morales, et al, 2016).…”
Section: Students' Learning Outcomes In Solving Exponential Expressions Using Peer Tutoringsupporting
confidence: 87%
“…Previous meta-analyses in the field by Ginsburg-Block, Rohrbeck, and Fantuzzo (2006) [51] and Ullah, Tabassum, and Kaleem (2018) [52] noted that peer tutoring usually has a positive impact on students' self-concepts, but the significance of the effect has yet to be proven. During the last several years, the latest studies of peer tutoring and students' self-concepts in reading [53], writing [54], English as a foreign language [55], physical education [56], physics [57], and chemistry [58] are promising but far for from being conclusive.…”
Section: Peer Tutoring and Self-conceptmentioning
confidence: 99%
“…In academic settings, learning strategies are related to the processes enacted by students at different levels (i.e., cognitive, metacognitive, affective, and behavioral) that facilitate the achievement of learning tasks. For instance, Ullah and colleagues [6] showed that academic performance could be significantly enhanced through peer tutoring, which leads to higher results in comparison to traditional lecture-demonstration methods. Hence, a teaching strategy based on the constant interaction within groups of students supported by a peer playing the role of a tutor may support the students' learning and lead to the attainment of higher grades.…”
Section: Learning Strategies and Academic Achievementmentioning
confidence: 99%